2012
DOI: 10.1200/jco.2012.30.4_suppl.199
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of FOLFIRINOX for first-line treatment of metastatic pancreatic cancer.

Abstract: ConclusionsCompared with gemcitabine, first-line folfirinox significantly prolongs median os. Given the favourable cost per qaly, the improvement in clinical efficacy, and the limited available treatment options, folfirinox represents an attractive cost-effective treatment for mpc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 10 publications
(12 reference statements)
0
20
0
Order By: Relevance
“…The costs associated with managing AEs during PC treatment are often considerable 23. Therefore, identification of the AE profile for real-world patients is quite relevant from an economic perspective.…”
Section: Discussionmentioning
confidence: 99%
“…The costs associated with managing AEs during PC treatment are often considerable 23. Therefore, identification of the AE profile for real-world patients is quite relevant from an economic perspective.…”
Section: Discussionmentioning
confidence: 99%
“…After the efficacy of gemcitabine was demonstrated in 1997, a UK study concluded that it was a cost-effective therapy [18]. A Canadian costeffectiveness evaluation compared FOLFIRINOX with gemcitabine using data from the ACCORD trial [19]. The authors demonstrated that FOLFIRINOX had an 80 % probability of being cost-effective at the $100,000/QALY threshold.…”
Section: Discussionmentioning
confidence: 96%
“…Society has indirectly placed a financial attribution to a quality adjusted life year (QALY), ranging from $50,000 to $150,000, depending on the source; frequently, these values reflect what Medicare will reimburse for a year of hemodialysis, or alternatively 2–3 times country‐specific per capita income . However, current chemotherapy regimens for pancreatic cancer fall both below (FOLFIRINOX) and above (Erlotinib) this threshold . But there has been no formal discussion or conclusion reached about a reasonable cost to avoid suffering.…”
Section: Discussionmentioning
confidence: 99%